Assessing the Organic Pollution and Aquaculture Activity of Surface water at Shatt-Al-Arab Estuary Southern of Iraq - Makia M. Al-Hejuje; Prof. Hamid Talib Al-Saad; Najah A. Hussain (Marine Science Department Diponegoro University, 2017)
Surface water samples were collected monthly from December, 2012 to November, 2013 at the middle part of Shatt Al-Arab Estuary at Basrah city during the low tide period to assess the organic pollution status using the Organic Pollution Index (OPI), and the aquaculture activities using Minimum Operator Concept (MOC). Results of biological oxygen demand (BOD5), ammonium, nitrite and orthophosphate were used to calculate OPI, while dissolved oxygen (DO), total phosphate and turbidity were used to calculate MOC. Results showed that OPI values range from 4.5 - 4.75 referred to weak organic–non organic pollution status. On the other hand, the water of Shatt Al-Arab Estuary can be considered as medium–excellent water for aquaculture activity according to the MOC range (66.67 - 93.33). Keywords: Estuary, Surface water, Organic Pollution Index, Aquaculture activity, Minimum Operator Concept